Building a scalable diabetic limb preservation program: four steps to success. Issue 1 (1st January 2018) - Khan, Tanzim; Shin, Laura; Woelfel, Stephanie; Rowe, Vincent; Wilson, Brittany L.; Armstrong, David G.
ABSTRACT: Over the past generation, limb preservation programs and diabetic foot services have begun to proliferate within academic health science centers as well as within health-care systems in general. We describe four key components for a successful program that, developed sequentially with temporal overlap, can allow the program to scale. The first component includes establishment of a 'hot foot line' for urgent emergency department/inpatient referral. The second includes development of a wound-healing clinic to address outpatient care through to remission. The third component focuses on the diabetic foot in remission to maximize ulcer-free days following healing. The fourth and final component focuses on implementation of local and widespread screening clinics to identify and triage patients into appropriate therapeutic and surveillance programs for healing, remission, and primary prevention. Along with developing each of these components, we describe discrete methods to quantify success.